Panda Bear in Africa [videorecording (DVD)] - Kiilerich, Karsten; Claus, Richard; Sprakling, Robert (Shout! Studios, 2025)
A fun and adventurous Panda travels from China to Africa to rescue his best friend dragon who has been kidnapped. On his journey, he discovers a completely unknown world and faces frightening hippos, suspicious hyenas, and wise gorillas. Relying on his wits (and some newfound friends) he makes his way across Africa, before rescuing his friend dragon and saving his new friends' jungle home. An exciting family comedy, a fish out of water/coming of age story.